Transgression of the rights of women and the LGBT community due to gender inequality in public office - Acosta-Toledo, Nicole; Vásquez-Lapeira, Mario; Pereira Ortega, Duanys Liesel (DIXI, 2022)
In addressing the problem of gender inequality in public office, it is possible to affirm that, despite the constant violation of rights that these two groups have suffered throughout history, today they enjoy greater participation at the highest decision-making levels of the branches of public power. However, the efforts of both women and the lgbt community to participate in democratic processes are undermined by the lack of implementation of public policies aimed at counteracting this problem. In the context of the current situation generated by the covid-19 pandemic, women and people belonging to the lgbt community have had fewer opportunities to develop in the labor sphere, thus exacerbating the gap between men and women in different fields of society, a gap that is evident even in the spheres of public power. Therefore, our research will answer the problem question: how does gender inequality in public office symbolize a transgression for the rights of women and the lgbt community in Colombia? Therefore, an analysis of gender inequality in public office as a determining factor for the transgression of women’s rights and the lgbt community will be carried out. Three specific objectives are addressed: (i) to describe the evolution of the effective participation of women and the lgbt community in public office in Colombia; (ii) to identify the factors that transgress the equal participation in public office; and (iii) to compare the measures applied in Sweden and Colombia to counteract gender inequality in public office. The above is in order to contribute to political pluralism and the consolidation of a true democracy in Colombia.